(untitled) (African Journal of Biomedical Research, 2022)
A descriptive cross-sectional survey was conducted among 384 pupils aged 5-12 years selected from 3 public primary schools using multi-stage sampling technique. Information on cognitive performance was collected using the Raven’s Standard Progressive Matrices. Food Frequency Questionnaire and 24-hour dietary recall were used to obtain dietary information while anthropometric data were sourced using weighing scales and height meters. The mean age of the respondents was 9.0 ± 1.8 years. The mean weight and height were 23.4±4.6kg and 1.25±0.1m respectively. 1.6% of the respondents had normal height-for-age (>1 SD), 92.7% were moderately stunted (-2 to -3 SD) and 5.7% were severely stunted (<-3SD). The Standard Progressive Matrices showed that primary 5 and primary 4 pupils had the highest and lowest mean cognition score of 24.5 and 19.4 respectively. Positive correlation was observed between weight of pupils and intake of Carbohydrate (0.228), Protein (0.142), Fiber (0.157), Folate (0.232), Iron (0.254) and Zinc (0.125). Similarly, significant correlation was also observed between vitamin A intake and Set B cognition scores. Height-for-age and BMI-for-age did not have a significant effect on cognition as shown in the study. However, correlation coefficient of (r=0.108; p<0.005) reveals that there is a weak but significant relationship between weight and Total Cognition Score (TCS). These findings suggest that Weight-for-height is a better anthropometric index for assessing relationship between nutritional status and cognition among school-aged children. Also, consumption of vitamin A-rich foods should be encouraged for cognitive development in the school age.